Physical Determinants of Golf Swing Performance: Considerations for Youth Golfers. Issue 4 (3rd August 2022) - Shaw, James; Gould, Zachariah I.; Oliver, Jon L.; Lloyd, Rhodri S.
ABSTRACT: In the sport of golf, club head speed has been associated with higher skill levels in golfers and lower overall scoring. Research has shown that club head speed is an important measure of golf swing performance that can be enhanced with appropriate strength and conditioning interventions. Understanding the determinants of club head speed can help inform the design of testing batteries for talent identification and talent development of youth golfers. This review aims to highlight the current literature surrounding the biomechanical and physical determinants of golf swing performance and to examine the available tests that can be used to test these determinants in youth golfers.